Using color histogram as the trait of retina biometric - Hao, Hao; Kumar, Dinesh Kant; Aliahmad, Behzad; Che Azemin, Mohd Zulfaezal; Kawasaki, Ryo (2013)
Retina biometric has applications on high security access control systems. The interference of lighting and deformation of viewpoint in the retina image acquisition have impact on the process of retina feature extraction and matching. In this paper, we propose a method using color histogram as the trait of retina biometric. The color histogram has shown the feature of deformation invariant. The enhancement using discrete wavelet transform decomposition minimizes the difference within the individuals and increases the correlation between the retinal images of the same person. This method provides a solution against the variation within the individuals and lower false rejection rate in the retina biometric.